Compliance with drug treatment among patients with tuberculosis in the Shiluvane Local Area, Mopani District. Limpopo Province - Mabitsela, Moorane Sarah (My University, 2012)
Tuberculosis (TB) is the cause of 1, 8 million deaths annually, 99% of the deaths occurs in the developing countries and among the poorest people of these countries. Studies between high and low income countries demonstrate that rates of TB are significantly higher in poorer populations. World Health Organization introduced DOTS as global strategy for providing TB services which was expected to be delivered primarily by government run public health services (Malmborg, Mann, Thomson, & Squire, 2006). AIM Investigate factors that influence compliance and non-compliance to treatment among patients on tuberculosis drug treatment. STUDY SITE This study was conducted in Shiluvane local area in Greater Tzaneen Municipality under Mopani District in Limpopo Province, South Africa. One district hospital, one health centre and five clinics were selected for this study: Dr CN Phatudi hospital, Shiluvane Health Centre, Moime, Lenyenye, Mogoboya, Maake and Lephepane Clinics. (v) STUDY DESIGN This is a quantitative and qualitative study as mixed methods were used to get a comprehensive research report. SAMPLING The sample size used 150 of a given population using Morgan and Krejcie table (1994). The case register was used to select respondents. The respondents were selected according to particular interval; each second name on the list was selected. Questionnaire and structured interview was selected for data collection. Questionnaires were distributed among clients who are able to read and write for them to complete, the researcher and the assistant helped to fill questionnaires for those who cannot read or write. The study was conducted at identified hospital, health center and clinics. RESULTS Education Level, the findings of this study displays that only 3,7% of participants hold tertiary qualifications, and 50% secondary education and 37,3% of primary education. Occupation, 76.4% of participants are unemployed. Income, 52,6% of participants earn between R1000-R2999 and 17,5% does not have income. (vi) CONCLUSION In conclusion based on the results and objectives of this study compliance with drug treatment among patients with tuberculosis in Shiluvane local Area, Mopani District, Limpopo province is 90.9%.
Thesis (MPH.) -- University of Limpopo, 2012
Keywords: Tuberculosis; Drug treatment; Tuberculosis; Tuberculolis -- Patients; Tuberculosis -- Treatment; Drug utilization; Drug use monitoring